Ultrasound and Sialendoscopy Findings in Radioactive Iodine–Induced Sialadenitis: Comparative Analysis and Possible Impact on Management - Koch, Michael; Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Iro, Heinrich; Sievert, Matti (Journal of Clinical Medicine, 2024)
Background: To assess the correlation/association between ultrasound and sialendoscopy findings in radioactive iodine therapy–induced sialadenitis (RAIS). Methods: Patients presenting with RAIS were investigated with ultrasound and sialendoscopy. Four pathologic ultrasound parameters and seven pathologic sialendoscopy parameters were retrospectively assessed. Correlations/associations between ultrasound and sialendoscopy findings and associations between the changes between the first and last ultrasound and sialendoscopy findings were assessed separately for the parotid (PG) and submandibular glands (SMG). Results: Sixty-seven patients were included. In the first examination, 107 glands were investigated (PGs 88.8%, SMGs 11.21%), and in the last examination, 64 glands were investigated (90.6% PGs, 9.4% SMGs). Highly significant positive associations were observed between the severity or category of ultrasound and sialendoscopy findings for first and last examinations for PGs (both p = 0.0001) and SMGs (p = 0.002; p = 0.037). Duct dilation had a significant negative association with the sialendoscopy findings for PGs in the first and last examinations (both p = 0.0001), but not for SMGs. Comparison of changes in the ultrasound and sialendoscopy findings between the first and last examinations showed a significant positive association for PGs (p = 0.0001) but not for SMGs. Conclusions: Ultrasound and sialendoscopy findings for the parenchyma and duct system in RAIS showed significant associations/correlations and can be useful for effective management in RAIS.
CRIS-Team Scopus Importer:2024-06-14
Keywords: radioactive iodine; salivary gland; treatment; ultrasound: sialendoscopy